(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article examines the role and importance of the Constitution in protecting the rights and freedoms of individuals at the pre-trial stage, the problems that arise in the application and implementation of these rights, and the proposals and recommendations for their solutions, based on the study of national legislation and other international practices. In addition, the normative legal acts regulating this area of law and the scope of their application, as well as reasonable considerations on expanding the scope of their application, and the development of legal awareness and legal culture of the population are presented.